Strategi Peningkatan Ketahanan Pangan pada Masa Pandemi COVID-19 melalui Penguatan Kearifan Lokal Di Kabupaten Badung Bali - Gede Wirata (Pusat Kajian Bali Universitas Udayana, 2022)
When the COVID-19 pandemic came to Bali, many people lost their jobs and had difficulty getting food. This article discusses strategy to increase food security in Badung Regency, Bali, during the COVID-19 pandemic through strengthening local wisdom. The research method used is descriptive qualitative. The research results indicate the role of stakeholders in food security in Badung Regency before and after the COVID-19 pandemic to build synergy between large and small food producers, seek supporting regulations and work on capital assistance, as well as strategies to increase food security in Badung Regency through strengthening local wisdom by seeking expansion of agricultural land involving the customary villages (desa pakraman) and farmer organization (subak); socialization to the working society who caused COVID-19 to switch professions to the agricultural sector. This article contributes in providing input for formulating a strategy to increase food security in Badung Regency during the COVID-19 pandemic.